Forms of Presupposition and Construction of Ideological Meaning in the Controversial News of the Animated Film "Merah Putih: One for All" on the Cnn Indonesia YouTube Channel - Umi Fitriani; Iib Marzuqi; Bisarul Ihsan (EDUJAVARE: International Journal of Educational Research, 2026)
One of the important studies in pragmatics is presupposition or presupposition. This study aims to identify the form of presumption and analyze the role of presumption in constructing the meaning of ideology in the controversial news of the animated film Merah Putih: One for All on the CNN Indonesia YouTube channel. The method used in this study is qualitative descriptive. Data analysis using Yule presumption theory includes existential, factual, lexical, structural, nonfactual, and counterfactual presumptions as well as Van Dijk's critical discourse analysis theory which includes macro, superstructure, and microstructure structures. Data was obtained using the free participation (SBLC) technique. Based on the results of the study, six forms of presumption were found, namely (13) existential presumption, (11) factual presumption, (1) lexical presumption, (1) structural presumption, (1) nonfactual presumption, and (1) confactual presumption. These preconceptions not only serve as an implicit linguistic element, but also play a role in building ideological constructions in the news. The emerging ideologies are (2) the ideology of mutual cooperation, (3) the ideology of nationalism, (4) the ideology of democracy, (2) the ideology of education, (1) the ideology of legitimacy, and (16) the ideology of professionalism which is built through discourse strategies at the macro, superstructure, and microstructure levels.